2011
DOI: 10.1007/s11099-011-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization of micropropagated plantlets induces an antioxidative burst: a case study with Ulmus minor Mill.

Abstract: In this article, the effects of increased light intensities on antioxidant metabolism during ex vitro establishment of Ulmus minor micropropagated plants are investigated. Three month old in vitro plants were acclimatized to ex vitro conditions in a climate chamber with two different light intensities, 200 µmol m -2 s -1 (high light, HL) and 100 µmol m -2 s -1 (low light, LL) during 40 days. Immediately after ex vitro transfer, the increase of both malondialdehyde (MDA) and electrolyte leakage in persistent le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Likewise, transfer of A. lebbeck plantlets under threefold (150 PPFD) light intensity than in vitro condition (50 PPFD) favours proper acclimatization of the plantlets as proved by the enhanced levels of photosynthetic parameters. Similar results have been reported in Gardenia jasmiinoides by Serret et al (2001) and Ulmus minor by Dias et al (2013). While, an increase in carotenoids level particularly signifies that plants sustained the light stress as play a key role in protecting of chlorophyll pigments under stress conditions (Ali et al 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, transfer of A. lebbeck plantlets under threefold (150 PPFD) light intensity than in vitro condition (50 PPFD) favours proper acclimatization of the plantlets as proved by the enhanced levels of photosynthetic parameters. Similar results have been reported in Gardenia jasmiinoides by Serret et al (2001) and Ulmus minor by Dias et al (2013). While, an increase in carotenoids level particularly signifies that plants sustained the light stress as play a key role in protecting of chlorophyll pigments under stress conditions (Ali et al 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Certain researchers also reported that cold stress increased the generation of ROS, including H 2 O 2 in plants, and as a result of this the MDA content could be also increased (Senaratna et al 2000;Kang et al 2003). In addition, it has been suggested that this effect of cold stress can disrupt the permeability of the cell membrane structure of the plant (Dias et al 2011). In the plants applied SA and then exposed to cold (SA + cold treatment), the MDA content was determined significantly to be decreased at all days (10, 17, 24 and 31) in comparison to respective cold values (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because, similar to other stresses, reactive oxygen species (ROS) such as superoxide anion (O − 2 ), CONTACT Salih Mutlu salihmutlu@yahoo.com H 2 O 2 and hydroxyl radicals ( · OH) are produced during response to cold stress (Mutlu et al 2009a(Mutlu et al , 2009bHu et al 2010). Toxic levels of ROS can impair membrane permeability (Dias et al 2011) by inducing lipid peroxidation (Mutlu et al 2011;Esim et al 2014), cause damage to DNA and proteins (Bertrand et al 2011;Kekec et al 2013) and ultimately lead to programmed cell death. These symptoms during cold stress have been evaluated as oxidative damage (Wang et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high irradiance, significant changes in the activity of the antioxidant enzymatic system were observed in micropropagated plants of Calathea (Dias et al 2011). …”
Section: Antioxidant Enzymesmentioning
confidence: 99%